Looking Back at Accident Compensation: An Australian Perspective - Luntz, Harold (Victoria University of Wellington Law Review, 2003)
Soon after ACC was enacted the momentum for comprehensive no-fault reform shifted to Australia, where another Commission led by Sir Owen Woodhouse extended the New Zealand principles to address all forms of incapacity, including sickness, in an integrated scheme. The proposed Australian ACC model suggests the radical potential contained in the original Woodhouse vision, even though political events in Australia followed a different course from those in New Zealand. This paper explains the evolution of the Woodhouse principles in the context of Australian policy and politics, and offers reasons why the proposed scheme never came to enactment.